Campaign contributions and local public goods in a federation - Ponce Rodríguez, Raúl Alberto (2018)
I develop a voting model of decentralized provision of local public goods (LPGs) with campaign contributions. I compare an economy with and without campaign contributions: in the former economy, local govern- ments do not provide Pareto efficient LPGs and do not maximize the welfare gains associated with matching LPGs with the inter-regional heterogeneity of preferences of voters. For the economy with campaign contributions, LPGs with and without spillovers are Pareto efficient, and the system of local governments maximizes the gains associated with matching LPGs with the inter-regional heterogeneity of prefer- ences.